Commentary on duty of candour and cancer screening - Given-Wilson, Rosalind (Br J Radiol, 2018)
English law mandates a duty of candour (DOC) for all healthcare providers. They must be open and honest when something goes wrong with care causing harm. Providers must apologize to those affected and investigate what happened. Screening is not 100% accurate and false positive and false negative results are inevitable. Guidance on DOC assists providers to judge when something has gone wrong in screening and the DOC legislation applies. DOC guidance helps distinguish such incidents from harms that are an expected and inevitable consequence of the imperfections of screening tests. For breast cancer screening the classification of interval cancers has been updated to take account of DOC. This guidance on DOC and classification of prior films of those presenting with interval cancers has relevance to other areas of diagnostic imaging. Review of prior examinations after a significant diagnosis has been made may reveal a previously overlooked abnormality.